Odpowiedź :
10-2×[(-1,6)+(-19,5):(-2½)]=10-2x[(-1.6)-7 4/5]=10-2x-9 2/5=
10-94/5=-44/5=8 4/5
23-3×[-2,4+(-14,7):4,5]=23-3*[-2,4-49/15]=23-3*(-17/3)=23-17=6
(-2,4×1,7+4,28):(2,75-3,45)=(-102/25+4.28)÷(-7/10)=-209/25÷(-7/10)=418/35
⅔×0,125+(-4,5)=1/12-4,5=-53/12=-4 5/12
-3⅔+(-14)=-53/3
(Myślę że dobrze ale na 100% tak do końca pewna nie jestem :P)
10-94/5=-44/5=8 4/5
23-3×[-2,4+(-14,7):4,5]=23-3*[-2,4-49/15]=23-3*(-17/3)=23-17=6
(-2,4×1,7+4,28):(2,75-3,45)=(-102/25+4.28)÷(-7/10)=-209/25÷(-7/10)=418/35
⅔×0,125+(-4,5)=1/12-4,5=-53/12=-4 5/12
-3⅔+(-14)=-53/3
(Myślę że dobrze ale na 100% tak do końca pewna nie jestem :P)
10-2×[(-1,6)+(-19,5):(-2½)]=10-2x[(-1,6)+(-39/2)x(-2/5)]=10-2x[(-1,6)+7,8]=10-2x[6,2]=10-12,4=-2,4
23-3×[-2,4+(-14,7):4,5]=23-3x[-2,4-3i12/45]=23-3x[-5i2/3]=23-3x[-17/3]=23-17=6
(-2,4×1,7+4,28):(2,75-3,45)=(-4i2/25+4i7/25):(2i3/4-3i9/20)=1/5:(2i15/20-3i9/20)=1/5:(-14/20)=1/5:(-7/10)=-2/7
⅔×0,125+(-4,5)=1/12-9/2=1/12-4i6/12=-4i5/12
-3⅔+(-14)=-17 i 2/3
napewno jest dobrze:)
23-3×[-2,4+(-14,7):4,5]=23-3x[-2,4-3i12/45]=23-3x[-5i2/3]=23-3x[-17/3]=23-17=6
(-2,4×1,7+4,28):(2,75-3,45)=(-4i2/25+4i7/25):(2i3/4-3i9/20)=1/5:(2i15/20-3i9/20)=1/5:(-14/20)=1/5:(-7/10)=-2/7
⅔×0,125+(-4,5)=1/12-9/2=1/12-4i6/12=-4i5/12
-3⅔+(-14)=-17 i 2/3
napewno jest dobrze:)